PENERAPAN MEDIA VIDEO PEMBELAJARAN DI ERA DIGITAL DALAM MENINGKATKAN MINAT BELAJAR SISWA - Nabila Qodrina; Imam Mashuri; Jon Iskandar Bahari (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Learning media is an important component needed in learning because it is a source of learning for educators and students. Learning media is not always in accordance with the conditions of students and learning materials, in this case the competence of an educator is needed to be able to determine the required learning media appropriately and appropriately. This study aims to describe the application of instructional media in increasing student interest in Islamic Cultural History in class X MAN 2 Banyuwangi. This study used a qualitative approach with a descriptive research type. Collecting data with the method of observation, interviews, documentation. The subjects in this study were teachers of the Islamic Cultural History subject and several class X MAN 2 Banyuwangi students. The sampling technique used is purposive sampling technique. For data validity using source triangulation. Data analysis using data reduction, data presentation, and drawing conclusions. Based on observations and interviews conducted by researchers, each teacher used a method that included planning, namely CP, TP, ATP, and modules. In practice, the teacher presents the material, shows learning videos, analyzes, records and conveys the core material obtained, discusses, and asks questions. Evaluation is closing and assessing. Supporting factors include adequate facilities and infrastructure, students play an active role, train thinking power, analytical skills. While the inhibiting factors are that it takes a long time, the ability to think and analyze students is different, it needs direction and material exposure.